EVALUATION OF VILLAGE-OWNED ENTERPRISE DEVELOPMENT POLICY FROM THE PERSPECTIVE OF REINVENTING GOVERNANCE IN THE DIGITAL ERA - Michael Agung Pranoto; Sri Roekminiati; Sri Kamariyah (International Journal of Multidisciplinary Reseach, 2026)
The growth in the number of Village-Owned Enterprises (BUMDes) in Indonesia has not been accompanied by comparable governance quality; recent data shows that only 75.8 percent of the tens of thousands of BUMDes are actually actively operating. BUMDes development policies have also been more oriented towards adding business units and technical digitization, rather than towards comprehensive governance arrangements. This study aims to evaluate BUMDes development policies through the perspective of reinventing governance integrated with digital era governance, in order to identify gaps between policy design and practice in the field. The study used a qualitative approach with a case study method in BUMDes Karya Mandiri, Ngoran Village, Blitar Regency. The study population included all BUMDes stakeholders, with a sample of five key informants selected purposively from the village government, BUMDes administrators, digital service managers, and community service users. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and conclusion drawing, accompanied by triangulation of sources and techniques. The results show partial policy implementation: the village government has acted as a catalyst and is results-oriented, but has not demonstrated strong evidence of empowerment and citizen ownership. In terms of digitalization, BUMDes services have only touched on administrative digitization, while reintegration of services and holistic citizen-centeredness have not been achieved, potentially creating a new digital literacy gap. The study concluded that BUMDes policy reform needs to be directed not only at increasing business units but also at strengthening citizen participation and equitable digital access.